A Brief History of Fascist Lies. - Finchelstein, Federico, 1975- (University of California Press, 2022)
""There is no better book on fascism's complex and vexed relationship with truth.""--Jason Stanley, author of How Fascism Works: The Politics of Us and Them In this short companion to his book From Fascism to Populism in History, world-renowned historian Federico Finchelstein explains why fascists regarded simple and often hateful lies as truth, and why so many of their followers believed the falsehoods. Throughout the history of the twentieth century, many supporters of fascist ideologies regarded political lies as truth incarnated in their leader.